In Vitro Chondrogenesis of Mesenchymal Stem Cells in Recombinant Silk-elastinlike Hydrogels - Haider, Mohamed (2007)
PURPOSE: In this study the chondrocytic differentiation and cartilage matrix accumulation of human mesenchymal stem cells (hMSCs) were investigated after encapsulation in a genetically engineered silk-elastinlike protein polymer SELP-47 K as an injectable matrix for delivery of cell-based therapeutics. MATERIALS AND METHODS: hMSCs were encapsulated in SELP-47 K and cultured for 4 weeks in chondrogenic medium with or without transforming growth factor-β3 (TGF). Chondrogenic differentiation was evaluated by histological, RNA and biochemical analyses for the expression of cartilage extracellular matrix components. RESULTS: Histological and immunohistochemical staining revealed that the cells acquired a rounded morphology and were embedded in significant amounts of chondrogenic extracellular matrix. Reverse transcriptase (RT)-PCR showed an up-regulation in aggrecan, type II and type X collagen and SOX9 in presence of TGF-β3. By day 28, constructs cultured in the presence of TGF-β3 exhibited significant increase in sulfated glycosaminoglycan and total collagen content up to 65 and 300%, respectively. CONCLUSIONS: This study demonstrates that SELP-47 K hydrogel can be used as a scaffold for encapsulation and chondrogenesis of hMSCs. The ability to use recombinant techniques to precisely control SELP structure enables the investigation of injectable protein polymer scaffolds for soft-tissue engineering with varied physicochemical properties.